2010
DOI: 10.1038/ejcn.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

Associations between habitual school-day breakfast consumption, body mass index, physical activity and cardiorespiratory fitness in English schoolchildren

Abstract: Objectives: The aim of this study was to assess associations between habitual school-day breakfast consumption, body mass index (BMI), physical activity (PA) and cardiorespiratory fitness (CRF). Methods: BMI, PA and CRF were measured in 4326 schoolchildren aged 10-16 years. Participants were classified as obese or non-obese, as having low or high PA and CRF. Habitual school-day breakfast consumption was assessed by a questionnaire and classified as never, sometimes or always. Results: Participants who sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
125
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 31 publications
(57 reference statements)
15
125
3
5
Order By: Relevance
“…Moreover, we observed that male and female breakfast skippers were less likely to have high cardiorespiratory fitness, both objectively measured and self-reported, than breakfast consumers. Similar results were observed by Sandercock et al (6) , although the authors failed to take into account the socio-economic status (e.g. educational level of parents and family affluence) as a potential confounder, which has been associated with breakfast consumption (2,32) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, we observed that male and female breakfast skippers were less likely to have high cardiorespiratory fitness, both objectively measured and self-reported, than breakfast consumers. Similar results were observed by Sandercock et al (6) , although the authors failed to take into account the socio-economic status (e.g. educational level of parents and family affluence) as a potential confounder, which has been associated with breakfast consumption (2,32) .…”
Section: Discussionsupporting
confidence: 83%
“…They did not find a significant relationship between eating breakfast and objectively measured physical activity (5) . In contrast, other authors showed higher levels of selfreported physical activity in those youngsters who were breakfast consumers (6,8) . The different methodology used to assess physical activity may explain differences among our findings and those previously observed.…”
Section: Discussionmentioning
confidence: 88%
“…In their study investigating breakfast, BMI and physical activity and fitness, Sandercock et al (14) succinctly summarised the relationship between eating breakfast and BMI: breakfast eaters have a lower BMI and better longterm weight control. However, as Sandercock et al (14) pointed out, the mechanisms by which breakfast influences BMI have so far not been identified. One likely reason for this is the cross-sectional design of the majority of studies, relying largely on self-reports, which cannot explore cause-and-effect relationships.…”
mentioning
confidence: 99%
“…Several lines of evidence have demonstrated benefits associated with regular breakfast consumption in children and adolescents, relating to academic performance (Lien, 2007), nutrition (Barton et al, 2005;Song et al, 2006), cardiorespiratory fitness and obesity (Sandercock et al, 2010). However, the relationship between breakfast and health benefits may not be because of consumption per se, but rather breakfast composition (Cho et al, 2003).…”
Section: Introductionmentioning
confidence: 99%